2016
DOI: 10.1177/014556131609500107
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Language Development and Affecting Factors in Children Aged 5 to 27 Months

Abstract: We conducted a study to assess the factors that affect language development in infants and toddlers using data obtained during developmental screening. Our study group consisted of 505 children–-244 (48.3%) boys and 261 (51.7%) girls, aged 5 to 27 months. The children were divided into four age groups: group 1, which we designated as the “6 months” group (age range: 5 to 7 mo); group 2, designated as the “12 months” group (11 to 13 mo); group 3, designated as the “18 months” group (17 to 19 mo); and group 4, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
2
4
1
1
Order By: Relevance
“…Zago et al 6 and Muluk et al 35 sought to further the discussion on areas with greater NPMD delay and found a greater prevalence of risks/delays related to language—which disagrees with the findings in the present research, whose sample did not have fails in language. However, according to Basílio et al, 36 stimuli presented by mothers during their time spent together can contribute to language development—which can be explained by the findings of the present research, as most of the sample spent most of their time with their mother.…”
Section: Discussioncontrasting
confidence: 99%
“…Zago et al 6 and Muluk et al 35 sought to further the discussion on areas with greater NPMD delay and found a greater prevalence of risks/delays related to language—which disagrees with the findings in the present research, whose sample did not have fails in language. However, according to Basílio et al, 36 stimuli presented by mothers during their time spent together can contribute to language development—which can be explained by the findings of the present research, as most of the sample spent most of their time with their mother.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous study concluded that children living in high socioeconomic areas had a less chance of delayed development of speech. 26 In current study delayed speech is seen more in higher income group. This could be due to increase the screen time, less attention by parents, more time spent with maids.…”
Section: Discussionsupporting
confidence: 44%
“…A positive relationship between the intra-variability of gross motor and language implies that both skills can be varied when the environment is adjusted. Muluk et al [ 48 ], in 2016, also found that language items were mostly correlated at 6 and 12 months. Both speech sounds and producing syllables were associated with social and gross motor development at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Both speech sounds and producing syllables were associated with social and gross motor development at 6 months. Furthermore, at 12 months, gross motor items such as standing by holding on were positively correlated with producing syllables for more than four words in the language items [ 48 ]. However, no correlation was found between the two variables in the control group of this study, displaying that the language development percentile is stable below the cutoff point (<16 percentiles).…”
Section: Discussionmentioning
confidence: 99%